2013
DOI: 10.1002/ppsc.201300296
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Evaluation of Nanoparticle–Protein Interactions by Dynamic Magnetic Susceptibility Measurements

Abstract: The use of dynamic magnetic susceptibility measurements is reported to study nanoparticle–protein interactions in situ. The technique consists of measuring the rotational diffusivity of thermally blocked magnetic nanoparticles (MNPs) in protein solutions. To illustrate the technique, the effect of nanoparticle zeta potential in carboxymethyl‐dextran‐coated MNPs and their interaction with model anionic and cationic proteins, such as bovine serum albumin (BSA), immunoglobulin G (IgG), fibrinogen (FIBR), apo‐tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…It is important to note that hydrodynamic diameters obtained from χ’ and χ” were not always the same even when the same model was applied to fit experimental data. These differences occur because the mathematical expression for χ” has a numerator that is directly proportional to the cube of the hydrodynamic diameter, thus making χ” more sensitive to changes in values of the hydrodynamic diameter relative to χ’ [37]. …”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that hydrodynamic diameters obtained from χ’ and χ” were not always the same even when the same model was applied to fit experimental data. These differences occur because the mathematical expression for χ” has a numerator that is directly proportional to the cube of the hydrodynamic diameter, thus making χ” more sensitive to changes in values of the hydrodynamic diameter relative to χ’ [37]. …”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that quantitative nanoscale viscosity measurements can be obtained from DMS measurements [46]. We have also used this technique to monitor phase transitions in the surrounding media, colloidal stability of MNPs in simple fluids, and adsorption of proteins to MNPs [47][48][49]. Others have also applied this technique to evaluate the mobility of nanoparticles in polymer hydrogels [50] and to evaluate the rheological properties of the suspending fluid [51].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, ACS measurements as a function of field frequency enable determination of the Brownian relaxation time and subsequently the hydrodynamic size of the particles using equation (2) above. Using this versatile characterization method, the formation of protein corona around MNPs caused by their surface charge 18,19 , the aggregation of MNPs within polymer nanocomposites 20 , and the mobility of MNPs in cells 19,21,22 , have been explored previously. Figure 1: Schematic showing the AC susceptibility versus frequency curve expected for blocked magnetic nanoparticles displaying Brownian relaxation.…”
Section: Introductionmentioning
confidence: 99%